Pengaruh Penambahan methanol Terhadap Emisi Bahan Bakar Mesin Sepeda Motor Berbahan Bakar Pertamax 150 CC - Fatkhurrozak, Faqih; Sanjaya, Firman Lukman; Syarifudin, Syarifudin; Hendrawan, Andre Budhi; Usman, M. Khumaidi; Gunawan, Gunawan (P3M Politeknik Negeri Cilacap, 2023)
Automotive vehicles have increased every year, especially motorcycles, which result in increased air pollution. The use of alternative fuel methanol is one of the solutions to control air pollution. methanol has a high oxygen content so it can improve emissions. This study aims to analyze the use of a mixture of Pertamax and methanol fuel on exhaust emissions using a 150 cc EFI gasoline engine. The percentage of methanol used in the test is 5%, 10%, and 15%. Variation of engine speed from 1000 to 3000 rpm with an interval of 1000 rpm. Measurement of exhaust emissions using a gas analyzer. The addition of methanol to Pertamax fuel reduced HC emission levels at PM15 by 34% at 3000 rpm and CO by 43% at 3000 rpm at PM15, while CO2 and O2 emission levels increased by 23% at 3000 rpm at CO2, mixing PM15 and at O2 emissions of 163% at a speed of 3000 rpm on PM5.